Catalogue baby : a memoir of infertility - Steinberg, Myriam (Page Two Books, 2021)
"A few months after Myriam Steinberg turned forty, she decided she couldn't wait any longer to become a mother. She made the difficult decision to begin the process of conceiving a child without a partner. With her family and friends to support her, she picked a sperm donor and was on her way. But Myriam's journey was far from straightforward. She experienced the soaring highs and devastating lows of becoming pregnant and then losing her babies... Unafraid to publicize her experiences, though, she found that, in return, friends and strangers alike started sharing their own fertility stories with her. Although the lack of understanding and language around fetal loss and grief often made it very hard to navigate everyday life, she nonetheless found solace in the community around her who rallied to support her through her journey. Through it all, Myriam remained hopeful and here she unflinchingly shares her story with wry humour, honesty, and courage."--